Pengembangan Media Pembelajaran Fisika Interaktif Berbasis Flash - Badrul Wajdi; Tsamarul Hizbi; Khaerus Syahidi (Kappa Journal, 2022)
This study aims to produce interactive physics learning media based on macromedia flash 8 straight motion material for Class VII students of SMP/MTs. This type of research uses the Research and Development (R&D) approach by adopting the ADDIE development model (Analyse, Design, Development, Implementation, and Evaluation). The design of learning media trials uses the Post-Test Only Control Group Design. The data collection instruments were material expert evaluation questionnaires, media expert evaluation questionnaires, science subject teacher evaluation questionnaires, student response questionnaires, multiple choice tests and student learning activity questionnaires. Data collection techniques were test techniques and observation techniques. Data analysis techniques are media feasibility test, normality test, variance homogeneity test and hypothesis testing. The results of the study from the aspect of the feasibility of learning media, media experts stated that it was feasible with an actual score of 75, material experts stated that it was feasible with an actual score of 73, teachers of science subjects stated that it was feasible with an actual score of 66, and the average response score of 4 students was 58.25 . While the research results from the aspect of learning media trials show that interactive physics learning media based on Macromedia Flash 8 is effective on student learning outcomes with an average experimental class score of 70.38 and classical learning mastery of 71.42%. The percentage of active students is in the good category with a percentage of 69.09%. When compared with the control class with an average value of 50.37 and 22.22% classical learning completeness. The percentage of active students falls into the moderate category with a percentage of 41.82%.